Fulminant hepatitis - Sinclair, Stephen (Springer Semin Immunopathol, 1990)
In conclusion, evidence exists that cellular and humoral immune-mediated processes result in hepatic necrosis in FH. Activation of the immune coagulation system appears to be an integral part of the inflammatory process resulting in fibrin thrombi which have been demonstrated in the liver, kidneys and lungs of patients with FH. A beneficial role of PG in the treatment of FH has been demonstrated, but controlled trials are required to firmly establish the efficacy of these agents. At present liver transplantation remains the treatment of choice in selected patients with FH. Further studies of the role of the immune system in the pathogenesis of this disease are required to devise more effective therapeutic strategies.